The Effect of Financial Stressors, Financial Self Efficacy on Financial Satisfaction through Financial Behavior as a Mediating Variable - Hadiyah; Nor Norisanti; Resa Nurmala (Dinasti Publisher, 2025)
This study is entitled The Effect of Financial Stressors, Financial Self-Efficacy on Financial Satisfaction through Financial Behavior as a Mediating Variable, with the object of research Gen Z in Sukabumi City. The purpose of this study is to analyze the effect of financial stressors and financial self-efficacy on financial satisfaction, with financial behavior as a mediator. The method used is quantitative approach with associative research type, involving 240 respondents selected using purposive sampling technique. Data were collected through an online questionnaire with a semantic differential scale, then analyzed using the SEM PLS method. The results showed that financial stressors have a significant negative effect on financial behavior and financial satisfaction, both directly and through financial behavior. Meanwhile, financial self-efficacy has a significant positive effect on financial behavior and financial satisfaction, both directly and indirectly. Financial behavior itself has a significant positive effect on financial satisfaction. The conclusion of this study is that financial behavior acts as an important mediator in strengthening the influence of financial self-efficacy and suppressing the negative impact of financial stressors on Gen Z financial satisfaction. This research is expected to provide new insights to improve the financial well-being of the younger generation in Sukabumi.